Development of an Online Supporting System Flood Warning for Vu Gia Watershed, Quảng Nam Province, Vietnam: Conceptual Framework and Proposed Research Techniques - Lợi, Nguyễn Kim; Liêm, Nguyễn Duy; Thiện, Phạm Công; Phận, Lê Văn; Tú, Lê Hoàng; Thủy, Hoàng Thị; Trai, Nguyễn Văn; Quỳnh, Trần Lê Như; Phúc, Lê Tấn; Huyền, Nguyễn Thị; Ấu, Nguyễn Thị Tịnh; Hồng, Nguyễn Thị; et al. (VNU Journal of Science: Earth and Environmental Sciences; Vol 29 No 1, 2013)
Abstract : Vu Gia Watershed is located in theCentral Vietnam where hurricanes pose a constant natural threat to human lives and physical infrastructure. Hydrological monitoring is considered as an effective tool to respond to high floods by preventing and mitigating the losses. The purpose of this study was to conduct and perform hydrological modeling to determine the flood-prone areas during the high rainfall season in the upstream Vu Gia Watershed. The methodology involved: hydro-climatic database building, a detailed Digital Elevation Model (DEM), a land use cover, and a soil map of the basin. With all these data, the SWAT model (Soil and Water Assessment Tool) was used to predict discharge values. These discharge values were used, along with the DEM, to predict flood hazard areas in the downstream of Vu Gia Watershed floodplains. This procedure was made using the HEC-RAS model (Hydrological Engineering Center-River Analysis System). The results show the exact location of areas with high, moderate and low risk, which are to be flooded at specific high floods. The results also provide the location in critical situation, so that an early warning system can be located. Additionally, as a part of this study, valuable information about how to prevent and mitigate the affects of flood-related damage was provided to residents at risk in the low land areas of the Vu Gia Watershed. Keywords: Flood warning, SWAT, HEC-RAS, Vu Gia Watershed, Quảng Nam Province.